2023
DOI: 10.1101/2023.04.23.23288980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facilitators and Barriers for Telemedicine Systems in India from Multiple Stakeholder Perspectives and Settings

Abstract: Telemedicine is viewed as a crucial tool for addressing the challenges of limited medical resources at healthcare facilities. However, its adoption in healthcare is not entirely realised due to perceived barriers. This systematic review outlines the critical facilitators and barriers that influence the implementation of telemedicine in the Indian healthcare system, observed at the infrastructural, socio-cultural, regulatory and financial levels, from the perspectives of healthcare providers, patients, patient … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Furthermore, cost-effective solutions, like reusable ICT resources, reduce the financial burden, making telemedicine more feasible and accessible, especially in resource-limited areas. These elements collectively enhance the quality, reach, and sustainability of telemedicine, significantly contributing to the transformation of healthcare delivery (16,21,25,26). This approach aligns with global trends in digital health and is crucial for creating a comprehensive and inclusive telemedicine environment in Zambia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, cost-effective solutions, like reusable ICT resources, reduce the financial burden, making telemedicine more feasible and accessible, especially in resource-limited areas. These elements collectively enhance the quality, reach, and sustainability of telemedicine, significantly contributing to the transformation of healthcare delivery (16,21,25,26). This approach aligns with global trends in digital health and is crucial for creating a comprehensive and inclusive telemedicine environment in Zambia.…”
Section: Discussionmentioning
confidence: 94%
“…It emphasizes the importance of standardized ICT systems, interoperability, secure data sharing, and cost-effective solutions (9). These elements are essential for the effective operation of telemedicine services (19)(20)(21) facilitating a unified and efficient telemedicine network that is accessible to all citizens. For instance, solid and reliable ICT systems are the backbone of telemedicine, supporting complex needs such as real-time communication and data management, and ensuring compatibility across various platforms (22).…”
Section: Discussionmentioning
confidence: 99%
“…The study also points out the advantages of telemedicine, such as cost savings and improved care coordination, while stressing the importance of compliance with data protection laws to ensure patient safety and quality of care. Venkataraman et al (2023) conducted a systematic review to identify the critical facilitators and barriers influencing the implementation of telemedicine in the Indian healthcare system. The study observed these factors from multiple stakeholder perspectives, including healthcare providers, patients, patient caregivers, society, health organizations, and the government.…”
Section: Stakeholder Implications: Healthcare Providers Patients and ...mentioning
confidence: 99%